Giant Macrocystic Lymphatic Malformation in a Neonate - Pinzon Uresti, Monica Andrea; Palacios Zertuche, Jorge Tadeo; Carrion Garcia, Ana Luisa; Lopez Rodriguez, Julio Cesar; Benavides Rodriguez, Juan Pablo; Garza Luna, Ulises de Jesus; Rodriguez Balderrama, Isaias (Journal of Neonatal Surgery, 2016)
Please see fulltext